Integrating Threat Intelligence into Real-Time Subdomain Risk Scoring Frameworks - Sanat Talwar, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
As cyber threats continue to evolve, ensuring the protection of subdomains against exploitation is a paramount challenge for enterprises. Current frameworks for evaluating subdomain risk primarily depend on static internal metrics, which restrict their responsiveness to emerging threats. This paper introduces a sophisticated framework that amalgamates various real-time threat intelligence sources, including VirusTotal, AbuseIPDB, and DNSDB, to augment the accuracy and scalability of risk scoring. By integrating dynamic external feeds with internal domain metrics, the framework offers a comprehensive and adaptable risk assessment model, empowering organizations to prioritize and address risks more effectively. Designed to scale for large enterprises with extensive subdomain frameworks, the proposed solution employs distributed processing and automation to provide real-time insights and responses.
Keywords: DNS; Threat Intelligence; Cybersecurity; Risk Scoring; Security Frameworks; Domain Name System; Real time Vulnerability Assessment